2018
DOI: 10.1111/all.13542
|View full text |Cite
|
Sign up to set email alerts
|

Are high‐ and low‐molecular‐weight sensitizing agents associated with different clinical phenotypes of occupational asthma?

Abstract: This large cohort study describes distinct phenotypic profiles in OA caused by HMW and LMW agents. There is a need to further explore differences in underlying pathophysiological pathways and outcome after environmental interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
75
1
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 38 publications
8
75
1
10
Order By: Relevance
“…The LMW-OA phenotype is currently associated with a higher prevalence of late asthmatic reaction on SIC, although the reaction was early in the present case. SIC did not significantly increase FeNO level, which is also described more frequently in this phenotype [9,10]. The postchallenge increase in the sputum eosinophil count was significant and similar to the value reported by previous studies [9], thus confirming the switch from the paucigranulocytic pattern to the eosinophilic inflammatory pattern induced by exposure to the causal agent.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…The LMW-OA phenotype is currently associated with a higher prevalence of late asthmatic reaction on SIC, although the reaction was early in the present case. SIC did not significantly increase FeNO level, which is also described more frequently in this phenotype [9,10]. The postchallenge increase in the sputum eosinophil count was significant and similar to the value reported by previous studies [9], thus confirming the switch from the paucigranulocytic pattern to the eosinophilic inflammatory pattern induced by exposure to the causal agent.…”
supporting
confidence: 86%
“…SIC did not significantly increase FeNO level, which is also described more frequently in this phenotype [9,10]. The postchallenge increase in the sputum eosinophil count was significant and similar to the value reported by previous studies [9], thus confirming the switch from the paucigranulocytic pattern to the eosinophilic inflammatory pattern induced by exposure to the causal agent. These data suggest that the sputum eosinophil count could be a better predictive biomarker of OA than FeNO level.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…While irritantinduced asthma is attributed to a non-immunological mechanism, sensitizing agents induce asthma through mechanisms which may or may not be type-2dependent. In fact, a recent study showed that both high-molecular-weight agents (with an IgE-mediated mechanism) and low-molecular-weight agents (with as yet undefined mechanisms) may generate eosinophilic or neutrophilic responses [15].…”
Section: Discussionmentioning
confidence: 99%
“…About 5-20% of adult-onset asthma cases are work-related occupational asthma (OA) [7,8]. More than 300 causative agents in OA have been identified and can be classified into high-molecular -weight (≥ 5000 g/mol) proteins of vegetal or animal origin, or low-molecular-weight (LMW) chemicals [9,10]. OA eosinophilic inflammation is a feature of asthma caused by high-molecular-weight proteins, but in LMW OA, which involves a poor steroid response, the neutrophilic inflammatory response is crucial [11].…”
Section: Introductionmentioning
confidence: 99%